Beta-Hydroxysteroid Dehydrogenase Genes in Orange-Spotted Grouper (Epinephelus coioides): Genome-Wide Identification and Expression Analysis During Sex Reversal - Xiao, Ling; Guo, Yin; Wang, Dengdong; Zhao, Mi; Hou, Xin; Li, Shuisheng; Lin, Haoran; Zhang, Yong (Frontiers in Genetics, 2020)
Beta-hydroxysteroid dehydrogenases (β-HSDs) are a group of steroidogenic enzymes that are involved in steroid biosynthesis and metabolism, and play a crucial role in mammalian physiology and development, including sex determination and differentiation. In the present study, a genome-wide analysis identified the numbers of β-hsd genes in orange-spotted grouper (Epinephelus coioides) (19), human (Homo sapiens) (22), mouse (Mus musculus) (24), chicken (Gallus gallus) (16), xenopus (Xenopus tropicalis) (24), coelacanth (Latimeria chalumnae) (17), spotted gar (Lepisosteus oculatus) (14), zebrafish (Danio rerio) (19), fugu (Takifugu rubripes) (19), tilapia (Oreochromis niloticus) (19), medaka (Oryzias latipes) (19), stickleback (Gasterosteus aculeatus) (17) and common carp (Cyprinus carpio) (27) samples. A comparative analysis revealed that the number of β-hsd genes in teleost fish was no greater than in tetrapods due to gene loss followed by a teleost-specific whole-genome duplication event. Based on transcriptome data from grouper brain and gonad samples during sex reversal, six β-hsd genes had relatively high expression levels in the brain, indicating that these genes may be required for neurogenesis or the maintenance of specific biological processes in the brain. In the gonad, two and eight β-hsd genes were up- and downregulated, respectively, indicating their important roles in sex reversal. Our results demonstrated that β-hsd genes may be involved in the sex reversal of grouper by regulating the synthesis and metabolism of sex steroid hormones.